2009
DOI: 10.1136/jcp.2008.058248
|View full text |Cite
|
Sign up to set email alerts
|

Histological patterns in drug-induced liver disease

Abstract: The diagnosis of drug-induced liver injury (DILI) is a challenging problem, often confounded by incomplete clinical information and the difficulty of eliciting exposure to herbal products, over-the-counter agents and toxins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
192
2
25

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 282 publications
(226 citation statements)
references
References 132 publications
(97 reference statements)
7
192
2
25
Order By: Relevance
“…Importantly, the abnormalities were not localized to a particular liver lobule or zone but instead were evenly distributed throughout the entire liver. The homogenous pattern of expression was distinct from most models of liver injury, which tend to affect either periportal or perivenous zones disproportionately, and suggested that the primary defect was intrinsic to hepatocytes (25).…”
Section: Resultsmentioning
confidence: 97%
“…Importantly, the abnormalities were not localized to a particular liver lobule or zone but instead were evenly distributed throughout the entire liver. The homogenous pattern of expression was distinct from most models of liver injury, which tend to affect either periportal or perivenous zones disproportionately, and suggested that the primary defect was intrinsic to hepatocytes (25).…”
Section: Resultsmentioning
confidence: 97%
“…The hallmarks of acute hepatocellular injury are inflammation and/or necrosis (34). Both inflammation (green arrows) and necrosis (yellow arrows) were found in liver tissues from the mice treated with T-DM1 at the dose of 30 mg/kg, whereas inflammation and necrosis were not observed in liver tissues from control mice (Table 1; Fig.…”
Section: T-dm1 Treatment Induces Inflammation and Necrosis In Liver Tmentioning
confidence: 99%
“…impredecibles, no dosis-dependiente, no reproducibles y afectan una pequeña proporción de pacientes (entre 1/1000 y 1/100 000 pacientes expuestos) (11)(12)(13)(14)(15)(16)(17).…”
Section: Reacciones Idiosincrásicas (Inmunes O Metabólicas)unclassified
“…La hepatotoxicidad intrínseca es menos común, mientras que la idiosincrásica es la más asociada con este evento adverso (12,(18)(19)(20). La histología hepática es la herramienta ideal para definir el patrón de toxicidad hepática; sin embargo, en la práctica clínica, la mayoría de las lesiones hepatotóxicas se clasifica de acuerdo con pruebas bioquí-micas (21).…”
Section: Reacciones Idiosincrásicas (Inmunes O Metabólicas)unclassified
See 1 more Smart Citation